Differences of oral health scoring among pregnant women at two basic emergency obstetric and neonatal services centers: a cross-sectional study - Kusumah, Azka Mudhiarahmi; Suwargiani, Anne Agustina; Susilawati, Sri (Padjadjaran Journal of Dentistry, 2025)
Introduction: In Indonesia, the prevalence of oral health issues remains high, reaching 63.4% in West Java. Differences exist between regions, with Bandung Regency at 64.67% and Bandung City at 47.88%. These regional disparities, influenced by social determinants such as access to care, socioeconomic status, and health literacy, contribute to unequal outcomes. Pregnant women are particularly vulnerable due to physiological and hormonal changes, with poor oral health increasing the risk of preterm birth, low birth weight, and preeclampsia. Community health centers (puskesmas), as primary care facilities emphasizing promotive and preventive services, employ the Oral Health Scoring (OHS) method to assess both felt and normative needs. This study analyzes the differences of oral health scoring among pregnant women at two basic emergency obstetric and neonatal services centers. Methods: A cross-sectional, comparative analytical quantitative design was used. The subjects were pregnant women attending the two puskesmas, selected by accidental sampling. Oral health status was assessed using the OHS method. Data were analyzed with an independent t-test to compare groups. Results: A total of 100 pregnant women participated, mostly aged 26–35 years. Half reported discomfort (50%) and nearly half were dissatisfied with appearance (48%), though most had no eating difficulties (67%). Normative findings showed 85% of the women had 1–8 decayed teeth, 54% of them had enamel erosion, and 19% of them had inflammation/ulceration. Significant differences were found in caries (p=0.020), erosion (p=0.005), and inflammation/ulceration (p=0.010), but not in occlusion. Overall, 75% of the women were categorized as healthy, with no significant difference between centers (p=0.253). Conclusion: There are differences in the examination of caries, wear, and inflammation among pregnant women. There are no differences found on OHS category results in two basic emergency obstetric and neonatal services centers